Patal Purir Bhasa Ek swalpa Alokita Adhyay (পাতালপুরীর ভাষা – এক স্বল্প আলোকিত অধ্যায়) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2023)
Today no country is crime free. Criminals are committing crimes everywhere. They connect with each other in their own language. We called this language Criminal World’s Language. This language is a social dialect and also local dialect. Professional criminals are use this language in their own manner. They use code to communicate with each other.  Antisocial also called this language in their own periphery. In different country this language is known in different name. such as in Japan it is called ‘INGO’. In Bengali it is also known by Disguise Language. Criminals are using slang language in their own world. About this world’s language common people are unaware. They can not realise the meaning of this kind of language. Criminals are always trying to keep the meaning of the language in their own world. Every word have different meaning. Each word also reflect different meaning. In this world if one word is use by different kind of criminal it should reflect different meaning. Pick pocketer, kidnappers, smugglers, gambler are use their own language to aware their partner about the situation, kind of work, place, police, target etc. it is also done in different manner. Criminal world language reflect the mentality of a criminal and their behaviour. Beside this it also reflect culture and manner of a criminal and its periphery. To know this world we should about this language.
Keywords: Disguise Language; different meaning; Criminals using their language; Patal Purir Bhasa